2017
DOI: 10.1007/s10815-017-0945-z
|View full text |Cite
|
Sign up to set email alerts
|

Significantly lengthened telomere in granulosa cells from women with polycystic ovarian syndrome (PCOS)

Abstract: This finding reinforced the association between telomere abnormalities and PCOS. Given the importance of telomere length in cellular proliferation, our findings provided novel insights into the pathophysiology of PCOS that abnormalities in telomere length possibly disturb folliculogenesis and subsequently result in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 34 publications
3
25
0
1
Order By: Relevance
“…However, studies differ in the type of association and correlation. Of the 7 studies reviewed, 3 studies showed a negative association between LTL and PCOS patients (35-37) while Wei et al demonstrated significantly longer GTL but a negative association between LTL and PCOS patients (56). Further, 1 study revealed significantly longer LTL in patients with PCOS (57).…”
Section: Telomere Length and Female Infertilitymentioning
confidence: 99%
“…However, studies differ in the type of association and correlation. Of the 7 studies reviewed, 3 studies showed a negative association between LTL and PCOS patients (35-37) while Wei et al demonstrated significantly longer GTL but a negative association between LTL and PCOS patients (56). Further, 1 study revealed significantly longer LTL in patients with PCOS (57).…”
Section: Telomere Length and Female Infertilitymentioning
confidence: 99%
“…It is important to note that, in order to determine the precise impact of the histopathological/hormonal changes on telomere length, telomeres should be measured in the granulosa cells of PCOS patients. In recent studies, telomere lengths were measured by qPCR in the leukocytes obtained from either PCOS patients or control subjects and no remarkable differences were detected [93,94,95]. However, the length of telomeres in the granulosa cells was found to be significantly longer in the PCOS group (1.57 ± 0.67) than in the controls (1.00 ± 0.37) [93] (Table 1…”
Section: Ovarian Function and Telomeres/telomerase Activity In Humansmentioning
confidence: 99%
“…POF is an irreversible pathologic loss of the ovarian function occurring before age 40 and leading to early female infertility [99]. The predominant clinical symptoms include premature menopause, primary ovarian failure, hypergonadotropic hypogonadism, and gonadal dysgenesis [37, 93]. In the ovary of POF patients, two main defects are observed: follicle dysfunction and follicle depletion [99].…”
Section: Ovarian Function and Telomeres/telomerase Activity In Humansmentioning
confidence: 99%
“…Written informed consent was obtained from all patients and the study was approved by the Ethics Review Board of the First Affiliated Hospital of Zhengzhou University on 20 th November 2014 (Reference: 2014-LW-1217). All of the PCOS patients were selected according to the Revised 2003 Consensus on Diagnostic Criteria: Oligo- and/or Anovulation, Hyper-androgenism and Polycystic Ovary [ 32 ]. All of the non-PCOS patients had normal ovarian morphology and regular menstrual cycles with male factor infertility.…”
Section: Methodsmentioning
confidence: 99%